Antioxidant and omega-3 fatty acid intake in the modulation of respiratory illness & asthma in children - Nikravan, Ramin (Curtin University, 2011)
Background and aim: Asthma is one of the major public health problems in Australia with prevalence in West Australian children reported up to 31%. The rise in asthma prevalence in Western societies may be related to changes in dietary habits, as diets are often low in antioxidant nutrients and omega-3 fatty acids (n-3) and high in omega-6 fatty acids (n-6).The association between antioxidants, fatty acids and asthma is however controversial and there is a need for further investigation to clarify the role of these nutrients on asthma.The aim of this study was to investigate the dietary exposures of n-3, n-6 and antioxidant nutrients proposed to have protective effects against asthma symptoms. Data gathered over fourteen years in a prospective pregnancy cohort study were analysed. We hypothesised that n-3 fatty acids and antioxidant nutrients (vitamins A, C, E, β-carotene antioxidants manganese and zinc) would be protective against asthma symptoms.Methods: The Western Australian Pregnancy Cohort (Raine) study is a longitudinal study following 2868 children from birth to 14 years of age. This project consisted of two analyses as part of the overall study. Study One was a cross-sectional analysis of 1531 children at age 14 identified as having current asthma (n=167) or no asthma (n=1364). Study Two was a longitudinal analysis from a subset of the overall study whereby children were identified as having current asthma or no asthma at eight (n=335) and 14 (n=242) years of age. Dietary information was collected from food frequency questionnaires (FFQ) in both studies and red blood cell fatty acid content was measured in children for Study One. Student’s t-tests and ANOVA allowed comparisons of food and nutrient intakes between children with asthma or no asthma for both studies. In Study One depending on the outcome of interest, multinominal or binary logistic regression was performed. In Study Two, food and nutrients that showed a significant difference between asthma groups in ANOVA analyses (p<0.05) were included in analysis of covariance (ANCOVA) to determine whether they made an independent contribution after adjustment for age, sex, BMI and total energy intake. The Bonferroni post hoc test was applied to control for false positive results.Results of Study One: The participants were 50.8% male (n=778) and 49.2% female (n=753). One hundred and sixty seven adolescents (10.9%) had asthma categorised as mild (4.0%), moderate (4.4%) or severe (2.5%). Two hundred and eighteen adolescents (14.2%) had current wheeze. The most common allergy outcome was atopy (44.5%) n= 682. The least common allergy outcome was eczema (10.7%).The large majority of dietary antioxidants and fatty acids tested were unrelated to asthma and asthmatic symptoms. However, after performing regression analysis and adjusting for potential confounders (BMI, age, gender and total daily energy intake) increased intake of vitamin C showed protective association with asthma (adjusted OR= 0.997, 95% CI= 0.994–0.999) and increased consumption of berry fruits showed protective effects on atopy (adjusted OR= 0.988, 95% CI= 0.976–0.999).Increased level of docosahexaenoic acid (22:6n3) in RBC membrane showed protective effects on BHR (adjusted OR= 0.814, 95% CI= 0.669–0.989). The adjusted ratio of n6:n3 showed detrimental association with asthma (OR= 1.072, 95% CI= 1.009–1.139) and wheezing episodes (OR= 1.064, 95% CI= 1.007–1.124).Results of Study Two: None of the antioxidant nutrients were shown to be associated with asthma. Unadjusted ANOVA analysis demonstrated a significant association between asthma diagnosis and arachidonic acid (20:4n6) (p=0.039). However, after performing ANCOVA and controlling for the confounders (age, sex, BMI and total energy) the association became non-significant (p=0.330). In crude analyses the n6:n3 ratio was higher for asthmatic adolescents at eight and 14 years (3.38) compared to those with no asthma (2.78) (p=0.013). This ratio remained significant after adjusting for the confounders (p=0.030)Conclusions: Study One and Two provide some evidence on protective effects of antioxidants and fruits on asthmatic symptoms in adolescents. We found that while controlling for potential confounders, increasing intake of vitamin C by 1 mg/day results in a 0.3% reduction in the risk of developing asthma. We demonstrated that for every 1 g/day increased intake of berry fruits there was 1.2% reduction in the risk of having atopy. We showed that by increasing 1 mmol/L in the level of docosahexaenoic acid in RBC membrane there was 18.6% reduction in the risk of having BHR. We also demonstrated that for every 1 unit increase in n6:n3 ratio, there was 6.4% increase in the risk of developing wheezing episodes and 7.2% increase in the risk of having asthma. Therefore, Our study suggests that the ratio of n6:n3 in diet may play a modulatory role in the expression of asthma, suggesting that promotion of increased total n-3 and reduced n-6 may protect against asthmatic traits in childhood and early adolescence.